Prince Dunduk. Commentary on Alexander sergEyevich Pushkin's epigram translated by Karel Havlíček Borovský - Fiala, Jiří (Bohemica Olomucensia, 2023)
Among the epigrams of Karel Havlíček Borovský is the Učený epigram z ruštiny (Learned Epigram from Russian), a translation of Alexander Sergeyevich Pushkin's Epigram od Dondukov-Korsakov (Эпиграмма на Дондукова-Корсакова), which in 1835 mocked Mikhail Alexandrovich Prince Korsakov, who was appointed that same year second vice-president of the Imperial Academy of Sciences in St Petersburg and chairman of its administrative committee. The conflict between A. S. Pushkin and Prince M. A. Dondukov-Korsakov was caused by the censorial interference, by which the prince, in his capacity as state censor, affected Pushkin's versified Tale of the Golden Cockerel (Cказка о золотом петушке, 1834) and Pushkin's History of Pugachev (История Пугачёва, 1834), although Tsar Nicholas I. has authorized this publication but under the title History of the Pugachev Revolt (История Пугачёвского бунта). His career is said to have been due to a homosexual affair he had as a young officer with Count Sergei Semyonovich Uvarov, president of the Imperial St Petersburg Academy of Sciences and Minister of National Enlightenment Sergei Semyonovich. The author of the article finds out under what circumstances K. Havlíček Borovský, during his stay in Moscow from 5 February 1843 to 6 July 1844 as a tutor in the family of the professor of Russian literature at Moscow University, Stepan Petrovich Shevyryov, became acquainted with the works of A. S. Pushkin and the above epigram, which he adequately translated into Czech.
Keywords: K. Havlíček Borovský; A. S. Pushkin; epigram; M. A. Dondukov-Korsakov; translation; Czech language